Comparison of lower limb biomechanics during single leg landing among female recreational players with and without history of ankle sprain - Sabri, Nur Neesa Adryana (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2021)
The purpose of this study was to compare the lower extremities’ (i.e., Ankle, Hip and Knee joint) kinetics (i.e., moments) and kinematics (i.e., angles) variables between two groups (i.e., n=15 with history and n=15 without history of ankle sprain) among recreational volleyball, netball and basketball athletes from Universiti Sains Malaysia, Health Campus. Kinetic and kinematic variables of the athletes were measured and identified at two phases of landing (i.e., Initial Contact and Maximum vGRF) using Qualisys Track Manager (v2.16) which consists of six motion capture camera and one Bertec force platform. Then inverse dynamic calculation for musculoskeletal model was conducted using V3D Pro software (v5). Athletes were instructed to do Single Leg Landing (SLL) for a total of three trials on the force plate. Independent T-test was used to evaluate if there was any significant differences across groups. Based on the test, there were significant different for hip angle at initial contact which group with history showed greater hip adduction (p=0.01) compare to group without history on frontal plane kinematics. For frontal plane kinetics, there were significances different (i.e., hip moment (p=0.04) and knee moment (p=0.03) at maximum vGRF and ankle moment (p=0.01) at initial contact) between groups. From the results, it showed that, female university athletes with history of ankle sprain landed with dynamic knee valgus (DKV) which the results shown hip adducted, knee abducted and ankle everted compared to those without history of ankle sprain. Therefore, coaches and players are suggested to include more training sessions that will focus on strength exercises for hip muscles, knee and ankle joint particularly among female athletes with history of ankle sprain.